Analyze a Policies for Higher Education Institutions in Electrical and Information Engineering - Eka Putra (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This paper deals with the process of identification of the needed changes within higher education to meet future challenges. The work is related with the work package Policy of the LLP SALEIE program “Strategic Alignment of Electrical and Information Engineering in European Higher Education Institutions”. The analysis includes a review of the needs and impact of administrative policy as it impacts the design, development, delivery, assessment and review of academic programmes. The final objective of this global task is to bring together policy administrators from institutions across Europe to review current practices and to identify examples of best practice, to build a common understanding of governance and policy implications on the strategic changes associated with the project, and create a centre for excellence in the policy area. The paper presents the designing process of a questionnaire regarding the above problems. The objective is to achieve as broad coverage of European higher education institutional responses as possible.